Design of FIR QMF bank using windowing functions - Kamislioglu, Bircan; Karaboga, Nurhan (IEEE Computer Society, 2014)
The past over the years, single or multi-dimensional signal processing applications, communication systems, biomedical signal processing, word coding, sub-band coding in applications such as efficient use filter banks; single filter instead of multiple custom filters come together with being designed. In this study, two-channel filter banks a special case known as the QMF (Quadrature Mirror Filter - Quarter-mirror filter) bank for the design of Kaiser, Chebyshev and Hanning windowing methods with the filter's cutoff frequency on the optimization of a design based were made. QMF bank design, failure to peak reconstruction error (Peak Reconstruction Error-PRA) is based. As a result of the ongoing applications designed filter banks belonging to the numerical results and comparisons are given. © 2014 IEEE.
Pencereleme yöntemleriyle FIR QMF bankasi tasarimi
2014 22nd Signal Processing and Communications Applications Conference, SIU 2014 -- 23 April 2014 through 25 April 2014 -- Trabzon -- 106053
Keywords: Cutoff frequency; Filter banks; Biomedical signal processing; Numerical results; Reconstruction error; Signal processing applications; Subband coding; Two-channel filter banks; Windowing function; Windowing methods; Design